2019
DOI: 10.3390/s19112475
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting Joint Base Station Equipped Multiple Antenna and Full-Duplex D2D Users in Power Domain Division Based Multiple Access Networks

Abstract: In this paper, we investigate power domain division-based multiple access (PDMA) to support the base stations (BS) equipped with multiple antennas to serve mobile users. Such a system deploys multiple input single output (MISO)-based wireless transmission and a full-duplex (FD) scheme. Furthermore, such MISO PDMA system consists of BS employing transmit antenna selection to reduce complexity in signal processing at the receivers. We distinguish two kinds of mobile users, device-to-device (D2D) users and tradit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 27 publications
(37 reference statements)
0
21
0
Order By: Relevance
“…dx. (20) in which (c) is obtained via integration-by-part and (d) is via substituting (10) into (19). Furthermore, by applying (11), we found that the above integrals are similar to (16) and thus can be solved similarly.…”
Section: Ergodic Capacity Of Xmentioning
confidence: 84%
See 1 more Smart Citation
“…dx. (20) in which (c) is obtained via integration-by-part and (d) is via substituting (10) into (19). Furthermore, by applying (11), we found that the above integrals are similar to (16) and thus can be solved similarly.…”
Section: Ergodic Capacity Of Xmentioning
confidence: 84%
“…In NOMA systems, successive interference cancellation (SIC) equipping at receivers is required to remove multi-user interference (MUI) caused by the same frequency channel providing multiplexing several users. Many advantages benefit from practical aspects of NOMA systems, where the compatibility of NOMA exhibits system enhancement together with 5G key technologies such as device-to-device networks [6,7], cognitive radio [8,9], multi-antenna system with beamforming scheme [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, cooperative communications have been actively studied, whose major benefits are wider cell coverage and higher spectrum efficiency (SE). Cooperative power domain non-orthogonal multiple access (CNOMA) have received a lot of attention as an example of cooperative communications [11]. In CNOMA, near users (NU) obtain their own signals by decoding the superposed signal and forward far users' (FU) signals to FUs who have weaker links with a base station (BS).…”
Section: Introductionmentioning
confidence: 99%
“…There are more than schemes related to multiple access have been introduced in the Third Generation Partnership Project Radio Access Network (3GPP RAN) meeting, such as sparse code multiple access (SCMA), 1 power‐domain NOMA, 2 interleave division multiple access (IDMA), 3 multi‐user shared access (MUSA), 4 and pattern division multiple access (PDMA), 5 to name a few. Several new techniques for multiple access have studied based on the concept of NOMA as investigations in previous studies 6‐10 . By arranging different power levels to the users operating in power‐domain NOMA, multiple users can operate in each subcarrier and the diversity on that subcarrier can be achieved.…”
Section: Introductionmentioning
confidence: 99%